The Role of Social Media Literacy and Use in Determining Emotional Wellbeing - Afy Shovmayanti, Noor; Rizky Putri, Nisrina Akbar; Ardiansyah, Ardiansyah (Jurnal Paradigma, 2024)
Social media life is where communication and individuals and communities are characterized through social media networks. Concerns about the adverse effects of social media have directed public attention to media literacy as a potential solution. The SMILE Model is an effort to equip social media literacy that can influence social media use (in terms of exposure and self-expression), ultimately positively impacting individual/adolescent well-being. The results showed that most respondents preferred video content and a combination of video and text. Influencers' influence also influenced the use of social media, but only 25% of respondents felt that influencers had a significant impact on their use. Good social media literacy involves cognitive understanding and emotional regulation to improve emotional well-being. Balanced and healthy social media use can reduce loneliness and increase social support.